Photoemission in the study of oxide superconductors - Golden, MS; Egdell, R; Flavell, W (1991)
Photoemission has the potential to yield important information about the electronic structure of high-temperature superconducting oxides. However, the surface specificity of the technique, combined with the chemical complexity of these oxides can lead to considerable problems in data analysis and interpretation. Here we review photoemission results for c-axis-oriented thin films of Bi2Sr2CaCu2O8-based materials, where the surfaces are prepared for photoemission studies by in situ oxygen annealing. The current status of photoemission studies of high-Tc oxides is surveyed, highlighting areas of controversy.